Quantifying Ecological Loss: Legal Recognition and Challenges In Climate Litigation - Afri, Obbie (UIN Sunan Gunung Djati Bandung, 2025)
As climate litigation widens in Indonesia, courts increasingly recognize and quantify “ecological loss,” yet enforcement remains the weak link. This article examines how Indonesian law defines ecological loss, how courts and experts measure it in practice (especially in land- and forest-fire cases), and why conversion from judgment to restoration frequently fails. Using doctrinal and comparative analysis, we map valuation methods grounded in Law No. 32/2009 and Permen LHK No. 7/2014 and benchmark them against the US NRDA/HEA model and the EU Environmental Liability Directive’s restoration-first approach. We find that courts often blur ecolosgical loss and remedial costs, rely on simplified carbon pricing, and face procedural barriers and execution bottlenecks. Although large awards exist, collections are rare and restoration outcomes are unclear. We propose litigation-centric reforms: a Supreme Court standard operationalizing Permen 7/2014 for evidence and methods; fast-track execution and ring-fenced restoration funds; and concise judicial guidance to avoid double counting. These steps would align valuation, judgment, and enforcement, so damages translate into verifiable ecological repair rather than symbolic numbers.